2016
DOI: 10.15408/etk.v15i1.3109
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of ROA, BOPO, and FDR to Indonesian Islamic Bank's Mudharabah Deposit Profit Sharing

Abstract: This study aims to determine the effect of profitability ratio (ROA) the cost-revenue ratio (BOPO) and financing to deposit ratio (FDR) toward profit sharing of time deposit mudharaba in Islamic banking in Indonesia. This research is a quantitative study using heading the entire population of Islamic banks in Indonesia and the sample was selected using purposive sampling method. Samples were obtained at 7 Islamic banks and research data in the form of quarterly reports Islamic Banks 2011-2014 period. The analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 1 publication
2
10
0
3
Order By: Relevance
“…Financing is the main source of income for Islamic banks, which in turn will contribute to profits. Harfiah et al (2016) found a positive effect of FDR on mudaraba deposits. Meanwhile, according to Adem (2015), in conventional banking, loan to deposit ratio (LDR) also encouraged banks to provide more funds, so that LDR influenced the amount of deposits.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Financing is the main source of income for Islamic banks, which in turn will contribute to profits. Harfiah et al (2016) found a positive effect of FDR on mudaraba deposits. Meanwhile, according to Adem (2015), in conventional banking, loan to deposit ratio (LDR) also encouraged banks to provide more funds, so that LDR influenced the amount of deposits.…”
Section: Resultsmentioning
confidence: 90%
“…Yulianto & Solikhah (2016) suspected that the amount of mudaraba deposits is influenced by the need for financing (FDR). Harfiah et al (2016) found a signifi-cant and positive influence between FDR and mudaraba deposits. H2: Financing to deposit ratio has a positive effect on mudaraba deposits.…”
Section: Introductionmentioning
confidence: 84%
“…Meanwhile, research (Sabtatianto & Yusuf, 2018) explains that ROA has a significant positive effect on mudharabah deposits. The research was supported by (Nofianti et al, 2015;Harfiah et al, 2016;Purwati & Wicaksana, 2019;Susanto, 2019;Sulfiyani & Mais, 2019;Pasaribu et al, 2019). Farianto (2014) found that ROA had a significant negative effect on mudharabah deposits.…”
Section: Introductionmentioning
confidence: 74%
“…Meanwhile, the results of the study (Sabtatianto & Yusuf, 2018;Sulfiyani & Mais, 2019) had an insignificant negative effect. Different research results were obtained (Harfiah et al, 2016), where BOPO had a significant positive effect on mudharabah deposits. These results are supported by research results (Pasaribu et al, 2019).…”
Section: Introductionmentioning
confidence: 88%
“…Penelitian Yogi dan Ramantha (2013) serta Lia dan Erawati (2015) menunjukkan rasio BOPO berpengaruh negatif pada profitabilitas. Hasil yang berbeda ditunjukkan oleh hasil penelitian Limpaphayom dan Polwitoon (2004) yang menyatakan bahwa tidak ada pengaruh antara rasio BOPO dengan ROA dan menurutHarfiah et al (2016), rasio BOPO berpengaruh positif signifikan terhadap ROA. modal intelektual juga memberikan hasil yang tidak konsisten terhadap profitabilitas perusahaan.…”
unclassified